Media Pembelajaran Berbasis Komik Untuk Meningkatkan Motivasi Belajar Siswa - Suliastika Candra Wati; Silviana Romadani Putri (Kampus Akademik Publiser, 2025)
A teacher is required to be able to be a communicator and facilitator in school. This is very sustainable with the learning process, especially student motivation. Currently, student motivation is quite minimal. This research aims to increase student motivation by using comic-based learning media. The method used in this research is literature review research with descriptive analysis technique. This research uses systematic literature review techniques to collect various data and materials sourced from previous scientifict journal articles within the last 10 years. This method is used to obtain theoretical and systematic information data. The research results show that comic-based learning media greatly influences students’ motivation in learning. In line with previous research, if students feel bored, of course student motivation will also decrease, which will reduce the effectiveness of learning and lead to failurw in the world of education. By using interesting media, students will develop a sense of curiosity independently and will try to explore related learning material.